PENGALAMAN KOMUNIKASI ADAPTASI MAHASISWA MINANGKABAU (Studi Fenomenologi Mengenai Komunikasi Adaptasi Mahasiswa Minangkabau Program Studi Di Luar Kampus Utama Universitas Padjadjaran Pangandaran) (KOMUNIKOLOGI : Jurnal Ilmiah Ilmu Komunikasi, 2022)
This research aims to find out about the communication adaptation experience experienced by Minangkabau students at PSDKU, Padjadjaran University, Pangandaran. The purpose of this study was to find out how the motives of Minang students migrated to Pangandaran, the communication experiences experienced by Minang students, and the meaning felt by Minang students during adaptation communication. This study uses a qualitative method with a phenomenological approach as a constructivism paradigm and in-depth interviews as a data collection technique. Interviews were conducted with Minangkabau students who study and migrate at PSDKU Unpad Pangandaran who have experience communicating directly with the surrounding community. The results of this study describe the motives underlying the Minangkabau PSDKU Unpad Pangandaran students to migrate, the experience of adaptation communication that has been felt, and the meaning formed from the ongoing adaptation process. This research is also based on aspects of: communication experience, meaning, motive, adaptation, communication barriers, cross-cultural communication, nonverbal communication, and communication style. Their desire and openness to adapt to a new culture allows them to comfortably migrate to a new environment.